The Influence of Funding Policy and Investment Policy on Financial Performance of Companies Listed on the LQ45 Index - Claudia, Melia; Haninun, Haninun (LPPPIPublishing, 2025)
The goal of this research is to examine the significance of the negative impact of funding policy on financial performance in companies listed on the LQ45 index, the positive impact of investment policy on financial performance in companies listed on the LQ45 index, and the positive impact of dividend policy on financial performance in companies listed on the LQ45 index. The hypothesis suggested in this study is that funding policy has a fairly detrimental impact on the financial performance of firms listed on the LQ45 index. Second, investment policy has a considerable favorable impact on the financial performance of firms featured on the LQ45 index. The analytical tool utilized in this study is SPSS25.